1997
DOI: 10.1046/j.1525-1438.1997.09742.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of failures in patients with stage I ovarian cancer: an Italian multicenter study

Abstract: Gadducci A, Sartori E, Maggino T, Zola P, Landoni F, Fanucchi A, Stegher C, Alessi C, Buttitta F, Bergamino C. Analysis of failures in patients with stage I ovarian cancer: An Italian multicenter study. Int J Gynecol Cancer 1997; 7: 445-450.The objective of this retrospective multicenter study was to assess the rates, times, sites, and risk factors for recurrences in 224 patients with surgical stage I ovarian cancer. Postoperative adjuvant treatment was given to 153 of these patients. One hundred and eighty-tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…[15][16][17][18][19] However, the working group was hesitant to recommend the incorporation of this factor into the staging system because of the current lack of uniformly accepted criteria for grading epithelial ovarian carcinoma. This lack of criteria is strikingly different from endometrial carcinoma, in which a defined criteria for grading is established as part of the staging system.…”
Section: Rationale For Recommendationsmentioning
confidence: 99%
“…[15][16][17][18][19] However, the working group was hesitant to recommend the incorporation of this factor into the staging system because of the current lack of uniformly accepted criteria for grading epithelial ovarian carcinoma. This lack of criteria is strikingly different from endometrial carcinoma, in which a defined criteria for grading is established as part of the staging system.…”
Section: Rationale For Recommendationsmentioning
confidence: 99%
“…However, the effectiveness of adjuvant treatment in adequately staged cases is still debated and optimal adjuvant chemotherapy has not yet been established [9,10]. Data from the literature about analysis of failures in patients with early stage ovarian cancer revealed that the median time to recurrence ranges between 11 and 29 months and that relapse involves more frequently the pelvis or abdomen than retroperitoneal lymph nodes [5,[11][12][13][14][15]. It is noteworthy that isolated pelvic failures represent 26-47% of overall recurrences [5,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Tumor grade was a prognostic factor only in a univariate analysis in the present study. However, tumor grade is the most powerful prognostic factor in the early stages of epithelial ovarian cancer and it is confirmed by many authors (23)(24)(25)(26)(27). However, since all patients in our study received postoperative adjuvant chemotherapy, neither FIGO-stage nor tumor grade were used to select patients to adjuvant treatment.…”
Section: Discussionmentioning
confidence: 51%